(untitled) (Journal of Governance and Development (JGD), 2019)
â€˜One Belt One Roadâ€™ and currently known as Belt and Road Initiative which mooted by Xi Jinping in 2013 has attracted many interests from others region in the world to participate. Malaysia and Indonesia are the part of Southeast Asia states that welcome this grand strategy. This is due to social infrastructure has built over hundred years ago through the classical silk road and also the beneï¬ts of technology, infrastructure, ï¬nancial assistance, ports and others from this cooperation for the connectivity. Therefore, this article argues that the ï¬‚ux of Chinaâ€™s ï¬nancial and investment that penetrate through this grand strategy has given a red alert of Malaysia internally to preserve of the state autonomy by implementing afï¬rmative maritime policy. Methodologically, this explanatory article uses both primary and secondary data. Primary data consists of an in-depth semi-formal interview with selected informants. While, accessing secondary data from a recent government report, current policies, book, journal, and relevant online sources. This article ï¬nds that the neighbor ASEAN country which is Indonesia has more proactive and innovative in terms of policy which is Global Maritime Fulcrume compares to Malaysia despite has a strong tie of relationship with China. Surprisingly, Malaysia does not have any single strong maritime policy such practice in Indonesia to counter any future challenges and impact from this cooperation and fragmented. Therefore, the proposition of this article is to encourage Malaysia in the formation of integrated maritime policy which takes into account from Indonesia experience in its Global Maritime Fulcrum policy.